2017
DOI: 10.1007/s00216-017-0371-1
|View full text |Cite
|
Sign up to set email alerts
|

Using MALDI-TOF MS imaging and LC-HRMS for the investigation of the degradation of polycaprolactone diol exposed to different wastewater treatments

Abstract: Polymers are used in high amounts in a wide range of applications from biomedicine to industry. Because of the growing awareness of the increasing amounts of plastic wastes in the aquatic environment during recent years, the evaluation of their biodegradability deserves special attention. In the past, most efforts were dedicated to studying the biodegradation of polyesters in soil and compost, while very little research has been conducted on their fate in wastewater. Here, we assessed the ability of bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Matrix‐assisted laser desorption/ionisation (MALDI) is a soft ionisation technique that is widely utilised for mass spectrometric (MS) analysis of various biomolecules, including proteins, 1,2 peptides, 3 oligosaccharides, 4 oligonucleotides, 5 and synthetic polymers 6,7 . Due to its high sensitivity and molecular specificity, MALDI has been the subject of intense and continuous research efforts in fields such as metabolomics, 8,9 clinical medicine, 10,11 phamacology, 12,13 plant sciences 14,15 and environmental sciences 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Matrix‐assisted laser desorption/ionisation (MALDI) is a soft ionisation technique that is widely utilised for mass spectrometric (MS) analysis of various biomolecules, including proteins, 1,2 peptides, 3 oligosaccharides, 4 oligonucleotides, 5 and synthetic polymers 6,7 . Due to its high sensitivity and molecular specificity, MALDI has been the subject of intense and continuous research efforts in fields such as metabolomics, 8,9 clinical medicine, 10,11 phamacology, 12,13 plant sciences 14,15 and environmental sciences 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…The ultra-high performance liquid chromatographyquadrupole time-of-flight mass spectrometer (UHPLC-qToF) is a recent type of spectrometer characterized by an ultra-high performance chromatographic separation of the molecular species that has been successfully employed for its fast, highresolution separations, high-resolution mass spectra and high sensitivity. Even if high resolution mass spectrometry as well as other spectroscopic methods were previously reported for the investigation of the environmental impact produced by pharmaceuticals and cosmetic formulations [23][24][25][26] to the best of our knowledge this is the first UHPLC-qToF "all-ions MS/MS" approach to perform metabolites fingerprints by untargeted data treatment of pharmaceutical formulation submitted to a readily biodegradability test and targeted analyses for deeper investigation of the readily biodegradation output.…”
Section: Introductionmentioning
confidence: 99%
“…Even if high resolution mass spectrometry as well as other spectroscopic methods were previously reported for the investigation of the environmental impact produced by pharmaceuticals and cosmetic formulations, [24][25][26][27][28] to the best of our knowledge, this is the rst UHPLC-qToF "all-ion MS/MS" approach to obtain metabolite ngerprints by untargeted data treatment of pharmaceutical formulation submitted to a ready biodegradability test and targeted analyses for deeper investigation of the readily biodegradation output.…”
Section: Introductionmentioning
confidence: 99%
“…It is also considered to be a powerful tool for synthetic polymers; however, MALDI-MSI in polymer applications is still limited, although the number of reports is increasing. [18][19][20][21][22][23][24][25][26][27] Conventional MALDI-MSI visualizes the spatial distribution of target compounds, which have specified m/z values, by extracting their mass images from the MSI raw data. This method is not suitable for synthetic polymers because they have a mass distribution.…”
Section: Introductionmentioning
confidence: 99%
“…However, the differences in spatial distribution were discussed in previous reports by comparing the mass images of several degrees of polymerization. [21][22][23]26,27 Kune et al suggested drawing the sum of mass images of chemically related compounds using KMD analysis. 28 They have successfully applied the method to find lipids, tetraalkylammoniums, polymers and lipopeptides in complex imaging mass data.…”
Section: Introductionmentioning
confidence: 99%